Кореляцiйнi функцiї кулонiвської пари - Vaskivskyi, V. I. (Publishing house "Academperiodika", 2019)
The correlation functions of two electrostatically interacting particles have been obtained for the first time, by using the direct algebraic method for finding the cross-correlation functions. The efficiency of this method has been demonstrated by finding almost all unknown elements of the decomposition matrices in the second-order approximation.